2018
DOI: 10.2486/indhealth.2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work rest scheduling for prolonged standing activity

Abstract: Prolonged standing can cause discomfort on the body of the workers and can lead to injury and occupational disease. One of the ergonomic intervention is through improving the work-rest scheduling. The purpose of this study are to identify the fatigue level from the perception of the worker and to investigate the impact of the work-rest scheduling to the standing workers for 12 h working time with a different gender. This study involved two methods which are self-assessment of the worker and direct measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, several scholarly articles have underscored the importance of periodic follow-up assessments to ensure their efficiency and sustainability (Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Lin et al, 2022;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021). In terms of sample size or participant selection, certain articles employed mathematical formula to ascertain sample size (Dhole et al, 2021;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Rostami et al, 2022;So et al, 2019) while others either utilized the inclusion and exclusion criteria (Alghadir et al, 2021;Alipour et al, 2021;Antwi-Afari et al, 2021;Esmaeili et al, 2023;Kee, 2022;Kong et al, 2023;Motamedzadeh et al, 2021;Rahman et al, 2019;Ramdan & Candra, 2021;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021) or did not explicitly specify their sampling approach (Anshasi et al, 2022;Arunkumar et al, 2019;Darliana et al, 2020). Further analysis of the years of publication showed that a total of nine articles were published in 2021, which was the highest between 2018 to 2023.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other proposals focus on the inclusion of short or large breaks during the workday [59], comparing active vs. passive breaks [60]. This kind of solution could be difficult to implement for manufacturing workers where the assembly chain cannot stop.…”
Section: Discussionmentioning
confidence: 99%